Virgin territory : representing sexual inexperience in film - McDonald, Tamar Jeffers (Contemporary approaches to film and television series., 2010)
"In Virgin Territory contributors consider virginity as it is produced and marketed in film. With chapters that span a range of periods, genres, and performances, this collection proves that although it seems like an obvious quality at first glance, virginity in film is anything but simple. The essays in Virgin Territory destabilize assumptions about virginity and connect moments of virginity in film to their larger social significance."--Jacket.